Coronary Vasospasm While Treating Supraventricular Tachycardia: Is Adenosine Really to Blame?. (10th April 2013) - Quevedo, Henry C.; Munoz-Mendoza, Jerson; Pinto Miranda, Veronica; Sequeira, Rafael F.
Abstract : Coronary artery spasm has been reported during adenosine stress testing. Herein, we describe a transient ST-segment elevation following adenosine therapy for supraventricular tachycardia. A 38-year-old male presented to the emergency department with palpitations. Electrocardiogram showed supraventricular tachycardia with short RP interval. Vagal maneuvers were unsuccessful. Adenosine was then administered in two successive injections of 6 and 12 mg dosages, respectively. A subsequent 12-lead electrocardiogram revealed ST-segment elevation in inferior leads with reciprocal changes. Coronary angiography disclosed nonobstructive coronary disease. A postprocedure electrocardiogram exhibited normal sinus rhythm with nonspecific T wave abnormalities. Cardiac biomarkers were elevated with a peak troponin I of 0.32. Echocardiogram depicted bicuspid aortic valve and normal systolic function. Electrophysiological study revealed a concealed left accessory pathway and successful radiofrequency ablation was performed. Given the dynamic changes in the electrocardiogram, we hypothesize that this event was most likely a coronary vasospasm. The mechanism of coronary spasm following adenosine injection remains uncertain. Potential mediators include K ATP channels and adenosine-2 receptors.